LIFE THREATENING ANAPHYLAXIS WITH CO-AMOXICLAV DESPITE HAVING A PREVIOUS TOLERANT EXPOSURE TO THE ANTIBIOTIC - Saleem, Huma; Malik, Sara Haider (Journal of Ayub Medical College Abbottabad, 2019)
Background: Co-amoxiclav is used as a routine prophylactic antibiotic in surgical procedures. We present a case of 61 years old lady came to outpatient clinic with a diagnosis of right sided lower alveolar tumour. A plan was made to proceed with a Right Marginal Mandibulectomy. She received Co amoxiclav as prophylactic antibiotic and was clinically uneventful. On further questioning there were many different occasions on which the patient had oral co amoxiclav with no complications or side effects. No known drug allergies or otherwise were documented. As a part of surgical antibiotic prophylaxis, Co amoxiclav 1.2 gm was given to patient at the time of induction. After the antibiotic administration patient started having bronchospasm with increased airway pressures and severe hypotension indicating anaphylactic reaction. The patient was resuscitated, recovered from the anaphylactic shock successfully and provided extended recovery in post anaesthesia care unit followed by High Dependency Unit for overnight monitoring. Every centre or ward that administers injectable antibiotics have to have a standard protocol for the management of allergy reactions. A timely fashion is mandatory to make the best use of the drugs available and emergency gadget ought to be in vicinity in case this type of state of affairs rise up. Keywords: co amoxiclav; anaphylaxis; alveolar tumour; mandibulectomy